OCCURRENCE AND ELIMINATION OF MYCOBACTERIUM TUBERCULOSIS SUBSTANCES IN SPOTTED DEER (AXIS AXIS) AT JUNGLE MAHAL ZOOLOGICAL PARK, JHARGRAM, INDIA - Chanchal Datta; Sulata Mondal; Sheik Fareed J (Exploratory Animal and Medical Research, 2024)
An increased rate of death of Spotted deer (Axis axis) at Jungle Mahal Zoological Park, Jhargram, West Bengal, India was observed. Many other spotted deer of the herd were observed losing body weight. Their body weight was reduced gradually despite the provision of optimum nutrients. During post-mortem examination of the dead spotted deer, typical tuberculosis findings were observed. Samples were sent to the laboratories and were found to be Mycobacterium tuberculosis (MTB) positive. Treatment of MTB was started accordingly. After the treatment phase, multiple samples were sent again to the laboratories and all the samples were negative as per the laboratory reports. It is the first positive report of MTB in Spotted deer in West Bengal, India.